Studies on mosquitoes (Diptera: Culicidae) and anthropic environment. 12- Host-seeking behaviour of Anopheles albitarsis s.l. in South-Eastern Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Daniel Marucci
Results obtained with Anopheles albitarsis s.l. catches mainly performed through human bait at the Ribeira Valley region, SP (Brazil), are reported. Two species of the complex were recognized, namely An. albitarsis s.s. and species B. This latter predominated both in the rice fields and in the dwelling environments. The crepuscular rhythms showed an unimodal sunset pattern with most blood-seeking females caught during dusk. The absence of differences between indoor and outdoor behavior was confirmed for both species of the complex.